KAJIAN POTENSI ANTIFUNGAL SENYAWA FENANTROLIN 1 TERHADAP ISOLAT Candida sp RESISTEN TERBINAFIN DENGAN METODE MICROBROTH DILUTION - , WIWID SANTIKO, dr. Titik Nuryastuti,Sp.MK. M.Si, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Fungus Infection especially Candida sp isolate, have a high mortality and morbidity in the world and Indonesia. Terbinafine as antifungal known cause resistance. The compound 1,10-Phenantroline has successfully differentiated to Phenantroline-1, which known have antibacterial and antiplasmodial effects. 1- 10,Phenantroline proved and binds to the metal complex form metal-phen complexes that bind to transtition metal ions, such as Cu2+, Mn2+ and Ag2+ and potentially as antifungal. Objective: To determine the potential of antifungal effect and Minimum Inhibitory Concentration (MIC) antifungal activity of Phenantrolin-1 against resistant strains of Candida sp with Terbinafine. Methods: Design of this study is descriptive experimental, used Microbroth Dilution method. Phenantrolin 1 with a concentration of 25